García-Mendoza, A.J., Sándoval-Gutiérrez, D. & Redonda-Martínez, R. (2020) Mixtecalia, a new monotypic genus of the subtribe Tussilagininae (Senecioneae, Asteraceae) from the state of Oaxaca, Mexico. Phytotaxa 438 (2): 119–129. - García-Mendoza, Abisaí Josué; Sandoval-Gutiérrez, Daniel; Redonda-Martínez, Rosario (Phytotaxa, 2020)
N/A